Relation Between Quality of Life of Mothers of Children With Cerebral Palsy and the Children's Motor Functioning, After Ten Months of Rehabilitation Relación entre la calidad de vida de madres de niños con parálisis cerebral y la función motora de los niños, después de diez meses de rehabilitación Relação entre a qualidade de vida de mães de crianças com paralisia cerebral e a função motora dos filhos, após dez meses de reabilitação - Cejane Oliveira Martins Prudente; Maria Alves Barbosa; Celmo Celeno Porto (Universidade de São Paulo, 2010)
This study aims to analyze the quality of life of mothers of children with cerebral palsy, correlated with the evolution of their children's gross motor function after ten months of rehabilitation. An observational, longitudinal study was carried out in Goiânia, Goiás, Brazil, involving 100 mothers and children with cerebral palsy. The children's motor function was evaluated using the Gross Motor Function Measure (GMFM) and the mothers' quality of life using the Medical Outcomes Study 36-item Short Form Health Survey (SF-36). After ten months of rehabilitation, the children's gross motor function had significantly improved (p<0.001), while the mothers only presented a significant improvement (p<0.001) in the bodily pain domain. The improvement in the motor function of children with cerebral palsy did not influence the changes in the mothers' quality of life. El objetivo de este estudio fue analizar la calidad de vida de las madres de niños con parálisis cerebral, correlacionándola con la evolución de la función motora gruesa de los niños, después de diez meses de rehabilitación. Se trata de un estudio de observación, longitudinal, realizado en la ciudad de Goiania, estado de Goiás, en Brasil, con 100 madres y sus hijos con parálisis cerebral. La función motora de los niños fue evaluada por la Medición de la Función Motora Gruesa (GMFM) y la calidad de vida de las madres por el Medical Outcomes Study 36-item Short Form Health Survey (SF-36). Después de diez meses de rehabilitación, los niños obtuvieron una mejoría significativa (p<0,001) en la función motora y las madres presentaron una mejoría significativa (p<0,001) apenas en el dominio dolor. La mejoría de la función motora gruesa de los niños con Parálisis Cerebral no influyó en los cambios ocurridos en la calidad de vida de las madres. O objetivo deste estudo foi analisar a qualidade de vida de mães de crianças com paralisia cerebral, correlacionando-a com a evolução da função motora grossa das crianças, após dez meses de reabilitação. Trata-se de estudo observacional, longitudinal, realizado em Goiânia, Goiás, Brasil, com 100 mães e seus filhos com paralisia cerebral. A função motora das crianças foi avaliada pela Medição da Função Motora Grossa (GMFM) e a qualidade de vida das mães pelo Medical Outcomes Study 36-item Short Form Health Survey (SF-36). Após dez meses de reabilitação, as crianças obtiveram melhora significativa (p<0,001) na função motora grossa e as mães apresentaram melhora significativa (p<0,001) apenas no domínio dor. A melhora da função motora grossa das crianças com paralisia cerebral não influenciou as mudanças ocorridas na qualidade de vida das mães.